Abundance, respiration, and feeding rates of freshwater invertebrates in the laboratory and field at increasing temperatures - Archer, Louise C.; Sohlström, Esra H.; Gallo, Bruno; Jochum, Malte; Woodward, Guy; Kordas, Rebecca L.; Rall, Björn C.; O'Gorman, Eoin J. (Dryad Digital Repository, 2019)
Contains: data on the abundance of Limnophora riparia, Potamophylax cingulatus, and Simuliidae in the Hengill geothermal stream system, Iceland, along with data on respiration rates of L. riparia and P. cingulatus, and feeding rate data of both species (on Simuliidae prey) in the laboratory and field across a gradient of temperatures. These datasets also contain information on the natal stream (IS = stream identifier), natal stream temperature, experimental temperature, mass, species, initial prey number, and experimental setting (laboratory or field) where appropriate.